The treasured thief - Foley, Ryan, 1974- (Campfire originals., 2011)
Ancient Egypt. In the time of the pyramids and pharaoh kings! A beautiful young princess has travelled to the grand capital of Memphis -- home to the legendary pharaoh Rhampsinitus. She has journeyed from the western lands in search of a husband. But while meeting with the local men, the princess becomes privy to a secret tale. It is a story of desperation, thievery, and murder. But it is also a story of family, sacrifice and love.